2012
DOI: 10.1115/1.4005973
|View full text |Cite
|
Sign up to set email alerts
|

A New, Iterative, Synchronous-Response Algorithm for Analyzing the Morton Effect

Abstract: SISRA is implemented in a Timochenko-beam-based finite-element rotordynamics software suite. SISRA analyzes the Morton Effect as a synchronous response problem with excitations from: (1) mechanical imbalance, (2) induced thermal bent shaft moments, and (3) mechanical imbalance that is induced by thermal bow. A general elliptical orbit can be decomposed into the sum of forward and backward circular orbits. As input, SISRA requires that, at a specified speed, equilibrium position, iv and orbit: (1) the predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…They utilized an orbit time averaged heat flux into the journal surface to evaluate the journal temperature differential and found that the temperature differential increases with rotor spin speed and vibration level. Childs and Saha [4] suggested reducing lubricant viscosity and reducing the overhung mass for the remedy of the Morton effect problem. Lee and Palazzolo [5] developed a Morton effect simulation algorithm based on the 2D FE bearing model.…”
Section: Introductionmentioning
confidence: 99%
“…They utilized an orbit time averaged heat flux into the journal surface to evaluate the journal temperature differential and found that the temperature differential increases with rotor spin speed and vibration level. Childs and Saha [4] suggested reducing lubricant viscosity and reducing the overhung mass for the remedy of the Morton effect problem. Lee and Palazzolo [5] developed a Morton effect simulation algorithm based on the 2D FE bearing model.…”
Section: Introductionmentioning
confidence: 99%